Pengaruh Citra Merek terhadap Keputusan Pembelian Air Minum Dalam Kemasan Merek Arthess PT. Lingga Harapan Jambi (Studi Kasus Di Kelurahan Tanjung Pinang Jambi Timur) - Riko Mappadeceng; Nur Fhaikhoh (Universitas Batanghari Jambi, 2022)
PT. Lingga Harapan Jambi is a company engaged in bottled drinking water. PT. Lingga Harapan produces two well-known brands, namely Arthess and Citra which have been labeled Halal MUI and have been registered with SNI and BPOM. The research methodology used is, the research uses a design using descriptive methods and quantitative methodes. The population in this study is the community in Tanjung Pinang Village, Jambi Timur, based on the survey results it is known that the number of people in Tanjung Pinang Jambi Timur Village is 13,209 population. Which consists of 6,703 men and 6,506 women. Simple regression analysis, hypothesis testing so that the determinant coefficient and t test. The object of this research is the community in Tanjung Pinang Village, Jambi Timur. Based on the results of the coefficient of determination, it can be seen that brand image has an influence on purchasing decisions of 65.7% while the remaining 34.3% is influenced by other variables not examined. Based on the results of the t-test regression, it can be seen that the t-count value 13,709 > 1,984 t table, which means that brand image has a positive and significant effect on purchasing decisions.